2006
DOI: 10.1055/s-2005-916202
|View full text |Cite
|
Sign up to set email alerts
|

Trichome Dynamics and Artemisinin Accumulation during Development and Senescence ofArtemisia annuaLeaves

Abstract: Artemisinin is a sesquiterpene lactone endoperoxide and an important antimalarial drug produced in Artemisia annua. To unravel the diverse processes determining artemisinin yield in A. annua crops, artemisinin accumulation during the development of individual leaves was studied in two field experiments. During the life cycle of a leaf, artemisinin was always present. Quantities were low at leaf appearance and increased steadily. In leaves studied until after senescence, maximum quantities and concentrations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 20 publications
6
79
0
1
Order By: Relevance
“…These and other changes were largely restricted to the juvenile leaves (Datasets S1 and S3 and Fig. S5), which are relatively dense in glandular trichomes (29) and exhibit high expression levels of terpene synthases (30). Recent attempts to silence AMORPHA-4,11-DIENE SYNTHASE expression in self-pollinating varieties of Artemisia annua resulted in increased levels of two nonamorphadiene sesquiterpenes, caryophyllene and copaene, which may be due to an elevated pool of farnesyl diphosphate acting as substrate for other sesquiterpene synthases in the glandular trichomes (25).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These and other changes were largely restricted to the juvenile leaves (Datasets S1 and S3 and Fig. S5), which are relatively dense in glandular trichomes (29) and exhibit high expression levels of terpene synthases (30). Recent attempts to silence AMORPHA-4,11-DIENE SYNTHASE expression in self-pollinating varieties of Artemisia annua resulted in increased levels of two nonamorphadiene sesquiterpenes, caryophyllene and copaene, which may be due to an elevated pool of farnesyl diphosphate acting as substrate for other sesquiterpene synthases in the glandular trichomes (25).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work had shown that early stage intermediates in the artemisinin pathway accumulate in young A. annua leaves, and, as they mature, artemisinin accumulates (25,29). To investigate the effects of the cyp71av1-1 mutation on artemisinin biosynthesis, we analyzed three leaf developmental stages: juvenile (leaves 1-5 as counted down from the apical meristem), expanding (leaves 7-9), and mature (leaves 11-13).…”
Section: Resultsmentioning
confidence: 99%
“…The relative importance of trichome densities or individual trichome productivity for explaining differences in artemisinin yield over crops is still largely unknown. No experimental data for studies on whole crops is available, but studies on individual leaves within a crop have revealed that trichome densities can partly explain the differences in artemisinin concentrations within a crop (Lommen et al, 2006). Genotype and environmental conditions also likely affect trichome densities.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental work was done using either an open pollinated Vietnamese selection (Bouwmeester et al, 1999;Wallaart et al, 2000;Bertea et al, 2005;Lommen et al, 2006) or the hybrid cultivar Anamed A3 (cf. Lommen et al, 2006), and was carried out at two locations (Achterberg and Wageningen) in The Netherlands; experiments included different planting densities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation